The “collages” of Enric Miralles (ARQUISUR Revista, 2014)
The photomontage of the catalan architect, Enric Miralles, were investigated by myself in my pHD thesis, achieved at the University of Catalunya, UPC, Barcelona. This paper begins with a brief introduction to the subject of the photomontage regard to their origins and evolution in Dadaism and Surrealism art, showing a continuity with the Cubism of Picasso and, subsequently the works of David Hockney, which were, no doubt a reference to the photomontage of Enric Miralles. The “collages” of Enric Miralles are a representative configuration and an outstanding way in the architecture universo and its design process. The analysis of their “collages” is of fundamental significance for the subjects of graphic representation and design approach, adding value in creative processes.
Keywords: architecture; photography; landscape; design process; representation